Core Python Programming - Chun, Wesley J. (E Rutherford : Prentice Hall PTR Old Tappan : Pearson Education [distributor], 2000)
Annotation Python is soaring in popularity, and it's no wonder: Python is fast, scalable, easy to learn, and combines the best aspects of scripting languages like Perl with the key advantages of object languages like Java. In this book, Yahoo! Internet software engineer Wesley Chun teaches experienced developers all they need to know to leverage all of Python's power -- fast . Like all Core Series books, Core Python Programming teaches via hundreds of industrial-strength code examples, all targeted at professional developers who want to leverage the skills they already have. Chun begins with a professional-level introduction to Python syntax, objects, and error handling; functions, classes, and built-ins. Learn the best techniques for handling I/O, manipulating Python objects, working with files, filesystems, and more. Core Python Programming delivers detailed real-world coverage of Web/Internet and network programming, including CGI applications, adding Python support to web servers, client/server applications, network I/O, encryption/decryption, integration with DBM databases, and much more. The book also contains a quick reference to the entire language.
Scholarly & Professional
Keywords: Python (Computer program language); Python (Computer Program Language); Computers -- Programming Languages -- Python; Engineering & Applied Sciences; Computer Science; Python (Langage de programmation); Python (Computer program language)